Keberadaan Telur Cacing pada Tinja Anak TK Pembina Desa Wani I Kecamatan Tanantovea Kabupaten Donggala: The Presence Of Worm Eggs In The Feces Of Children At Pembina Kindergarten, Wani I Village, Tanantovea District, Donggala Regency - Sasmita, Hanum; Sapriana, Sapriana (Media Publikasi Cendekia Indonesia, 2025)
Background: Worm infections caused by Soil-Transmitted Helminths (STH), primarily from the Nematoda class, remain a public health concern. In 2023, the Mass Drug Administration (MDA) report in Wani Village, Tanantovea District, Donggala Regency, Central Sulawesi, noted that out of 3,739 targeted children aged 1–12 years, 3,704 received deworming treatment—achieving a 97% coverage rate. Among them, 1.33% were kindergarten-aged children. Aims: This study aimed to determine the presence of worm eggs in the feces of children attending Pembina Kindergarten in Wani I Village. Methods: A descriptive study was conducted from May 15 to June 7, 2024, involving all 36 children at the kindergarten. Stool samples were examined using the centrifugation method to identify STH eggs. Data were analyzed and presented in tabular form. Results: No worm eggs were found in any of the samples. Conclusion: Although no infections were detected, preventive measures remain essential. Teachers should continue encouraging biannual deworming, regular handwashing, consistent toilet use, and the use of footwear during outdoor activities to reduce future infection risks.